PERSEPSI MANAJEMEN TERHADAP PENERAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) REPORTING: STUDI KUALITATIF PADA PERUSAHAAN NON-KEUANGAN - Rinaldi, Eldian (PT. Samudra Solusi Profesional, 2026)
The increasing demand for corporate transparency and accountability has encouraged companies to adopt Environmental, Social, and Governance (ESG) reporting as part of non-financial disclosure practices. For non-financial companies, ESG reporting is not only driven by regulatory pressure but also by expectations from investors, stakeholders, and the public. This study aims to explore management perceptions toward the implementation of ESG reporting in non-financial companies. This research employs a qualitative descriptive approach using a case study method. Data were collected through in-depth semi-structured interviews, observation, and document analysis involving managers who are directly involved in sustainability and reporting activities. Data analysis was conducted using thematic analysis to identify key patterns and meanings related to ESG reporting practices. The findings indicate that management perceives ESG reporting as a strategic instrument to enhance corporate legitimacy, reputation, and long-term sustainability. However, challenges such as data availability, measurement complexity, and limited internal capabilities remain significant barriers. This study contributes to the ESG literature by providing in-depth insights into managerial perceptions and offers practical implications for improving ESG reporting practices in non-financial companies